Overexpression of the MSK1 Kinase in Patients With Chronic Lung Allograft Dysfunction and Its Confirmed Role in a Murine Model. Issue 6 (June 2021) - Nemska, Simona; Daubeuf, François; Obrecht, Adeline; Israel-Biet, Dominique; Stern, Marc; Kessler, Romain; Roux, Antoine; Tavakoli, Reza; Villa, Pascal; Tissot, Adrien; Danger, Richard; Reber, Laurent; et al.
Abstract : Background: Chronic lung allograft dysfunction (CLAD) and its obstructive form, the obliterative bronchiolitis (OB), are the main long-term complications related to high mortality rate postlung transplantation. CLAD treatment lacks a significant success in survival. Here, we investigated a new strategy through inhibition of the proinflammatory mitogen- and stress-activated kinase 1 (MSK1) kinase. Methods: MSK1 expression was assessed in a mouse OB model after heterotopic tracheal allotransplantation. Pharmacological inhibition of MSK1 (H89, fasudil, PHA767491) was evaluated in the murine model and in a translational model using human lung primary fibroblasts in proinflammatory conditions. MSK1 expression was graded over time in biopsies from a cohort of CLAD patients. Results: MSK1 mRNA progressively increased during OB (6.4-fold at D21 posttransplantation). Inhibition of MSK1 allowed to counteract the damage to the epithelium (56% restoration for H89), and abolished the recruitment of MHCII + (94%) and T cells (100%) at the early inflammatory phase of OB. In addition, it markedly decreased the late fibroproliferative obstruction in allografts (48%). MSK1 inhibitors decreased production of IL-6 (whose transcription is under the control of MSK1) released from human lung fibroblasts (96%). Finally, we confirmed occurrence of a 2.9-fold increased MSK1 mRNA expression in lung biopsies in patients at 6 months before CLAD diagnosis as compared to recipients with stable lung function. Conclusions: These findings suggest the overall interest of the MSK1 kinase either as a marker or as a potential therapeutic target in lung dysfunction posttransplantation. Abstract : Supplemental Digital Content is available in the text.